3(w-2)(-w-8)=0

Simple and best practice solution for 3(w-2)(-w-8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(w-2)(-w-8)=0 equation:


Simplifying
3(w + -2)(-1w + -8) = 0

Reorder the terms:
3(-2 + w)(-1w + -8) = 0

Reorder the terms:
3(-2 + w)(-8 + -1w) = 0

Multiply (-2 + w) * (-8 + -1w)
3(-2(-8 + -1w) + w(-8 + -1w)) = 0
3((-8 * -2 + -1w * -2) + w(-8 + -1w)) = 0
3((16 + 2w) + w(-8 + -1w)) = 0
3(16 + 2w + (-8 * w + -1w * w)) = 0
3(16 + 2w + (-8w + -1w2)) = 0

Combine like terms: 2w + -8w = -6w
3(16 + -6w + -1w2) = 0
(16 * 3 + -6w * 3 + -1w2 * 3) = 0
(48 + -18w + -3w2) = 0

Solving
48 + -18w + -3w2 = 0

Solving for variable 'w'.

Factor out the Greatest Common Factor (GCF), '3'.
3(16 + -6w + -1w2) = 0

Factor a trinomial.
3((2 + -1w)(8 + w)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(2 + -1w)' equal to zero and attempt to solve: Simplifying 2 + -1w = 0 Solving 2 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1w = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1w = 0 + -2 -1w = 0 + -2 Combine like terms: 0 + -2 = -2 -1w = -2 Divide each side by '-1'. w = 2 Simplifying w = 2

Subproblem 2

Set the factor '(8 + w)' equal to zero and attempt to solve: Simplifying 8 + w = 0 Solving 8 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + w = 0 + -8 Combine like terms: 8 + -8 = 0 0 + w = 0 + -8 w = 0 + -8 Combine like terms: 0 + -8 = -8 w = -8 Simplifying w = -8

Solution

w = {2, -8}

See similar equations:

| 3x-7y-4=0 | | 16+19=51 | | x^2+2x-3=x | | 3x+10+7x=20 | | 15-5=4 | | f(3)=-2x-5 | | 4n+8=8n-24 | | 9(3n-2)=(4n+5)+1 | | 5y+2y=2y-8 | | y^2-5y=-y-3 | | 12x^2-6x-5=0 | | x^2-6x+5=-2 | | -3x^2-8+6=0 | | 4+42x=28x+28 | | -2x^2+12x+12= | | 0.5(x-6)+1=2(x-10)-4 | | -2x+12x+12= | | (-17+9)y=0 | | 6x+24x^2=0 | | 2(-6+7x)=-138 | | -5(3x+2)=-3(x+2) | | -4y-28=12 | | -3(-5x+9)=48 | | 9-=25 | | -2(-5-6x)=-14 | | 3(-5+6x)=-15 | | -17-9y=0 | | 6(-6-2x)=96 | | -5(7x+7)=-175 | | 5(2+3x)=-140 | | 3+1=n+3 | | 3(1x+4)=6 |

Equations solver categories